1983
DOI: 10.1111/j.1365-2621.1983.tb14902.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative GLC‐MS Analysis of Phenolic Acids of Selected Tree Nuts

Abstract: Phenolic acids were extracted from the nutmeats and/or testae of pine nut, almond, filbert, American Chestnut, a hybrid American chestnut, Chinese chestnut, black walnut, butternut and shagbark hickory and analyzed as their methyl esters/trimethylsilyl derivatives by GLC-MS. Both qualitative and quantitative differences were observed among samples in the acids present with gallic acid being predominant except in pine nut, almond and filbert. Caffeic was the predominant acid in pine nut; protocatechuic acid was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 9 publications
2
39
0
Order By: Relevance
“…The walnut globulin fraction, second to glutelin, contributed 17.6% of the total solubilised protein, followed by albumin (6.8%) and prolamin (5.5%). Since walnuts contain appreciable amounts of phenolic compounds that are soluble in aqueous solvents, 33 it is possible that the solubilised phenolic compounds may bind with walnut proteins. Such binding of phenolic compounds in turn may make normally soluble proteins less soluble (or insoluble) in water or dilute salt solutions.…”
Section: Results and Discussion Chemical Compositionmentioning
confidence: 99%
“…The walnut globulin fraction, second to glutelin, contributed 17.6% of the total solubilised protein, followed by albumin (6.8%) and prolamin (5.5%). Since walnuts contain appreciable amounts of phenolic compounds that are soluble in aqueous solvents, 33 it is possible that the solubilised phenolic compounds may bind with walnut proteins. Such binding of phenolic compounds in turn may make normally soluble proteins less soluble (or insoluble) in water or dilute salt solutions.…”
Section: Results and Discussion Chemical Compositionmentioning
confidence: 99%
“…Amongst the identified phenolic acids, p-coumaric acid was most abundant in hazelnut kernel, hazelnut green leafy cover, and hazelnut tree leaf, whereas gallic acid was most abundant in hazelnut skin and hazelnut hard shell (Alasalvar et al, 2006(Alasalvar et al, , 2009. However, in a previous study, protocatechuic acid was reported to be the predominant phenolic acid in testa (skin) of hazelnut (Senter, Horvat, & Forbus, 1983). Amaral et al (2005) identified and quantified four phenolic acids, namely, 3-caffeoylquinic acid, 5-caffeoylquinic acid, caffeoyltartaric acid, and p-coumaroyltartaric acid, in hazelnut leaves from 10 different cultivars grown in Portugal.…”
Section: Hazelnutmentioning
confidence: 96%
“…Among the identified phenolic acids, p-coumaric acid was most abundant in hazelnut kernel, hazelnut green leafy cover, and hazelnut tree leaves, whereas gallic acid was most abundant in hazelnut skin and hazelnut hard shell, possibly implying the presence and perhaps the dominance of tannins in the latter samples. Senter et al (1983) compared phenolic acids of nine edible tree nuts produced in the United States. The extracts from the nut samples showed great diversity in the phenolic acids present.…”
Section: Hplc Analysis Of Free and Bound Phenolic Compounds In Brazilmentioning
confidence: 99%